Cultural omnivorousness in Turkey. (November 2017) - Rankin, Bruce; Ergin, Murat
Recent cultural consumption research has drawn attention to the emergence of the high status 'cultural omnivore, ' that is, individuals who consume a wide range of cultural products, including the expected 'high culture, ' but more 'popular' forms as well. Initially reported in studies conducted in the developed West, this study broadens the basis of comparison by investigating the case of Turkey – a non-western, predominantly Muslim, developing country with a long history of state-led westernization. Using data from a nationally representative survey of adults, the study examines 34 cultural tastes in three domains – music, food, and literature – and participation in five different cultural activities for evidence of an omnivorous pattern. The items used include indicators of 'high' and 'popular' culture, as well as 'local' and 'global/western' culture. The results of a latent class analysis clearly identify an omnivorous group. A distinctive feature of the Turkish cultural field is that groups are largely defined by their orientation towards local versus global forms, with omnivores consuming both, in contrast to groups that restrict their diet to 'local' forms. Further analysis shows that, similar to studies in other contexts, Turkish omnivorousness is associated with higher social position, especially education and income. Omnivores also tend to be younger and more secular in their views towards the role of religion in the public sphere. The article concludes that, in addition to the high/popular distinction, the local/global is a critical symbolic boundary shaping cultural identities in Turkey.